Entrepreneurial Self-Efficacy dan Technology Acceptance Model dalam Analisis Niat Adopsi AI untuk Pemasaran Digital Santripreneur Mahasiswa - Mohammad Haidar Ali; Rohmad Prio Santoso; Lilis Sugi Rahayu Ningsih; M. Syahru Ramadhan (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The ongoing digital transformation presents vast opportunities for Indonesian MSMEs, particularly santripreneurs within pesantren, to integrate artificial intelligence (AI) into their marketing strategies. This study explores how entrepreneurial self-efficacy (ESE) strengthens the Technology Acceptance Model (TAM) in the adoption of AI-based marketing. Employing a quantitative design, data were gathered from 375 student santripreneurs across five Islamic cities in East Java and analyzed using SEM-PLS. The results indicate that ESE exerts a positive effect on perceived ease of use and perceived usefulness, which subsequently enhance attitudes and adoption intentions. These findings underscore ESE’s significance as an external construct enriching the classical TAM. The study extends TAM within the pesantren entrepreneurship context and offers practical insights for promoting digital literacy training and ecosystem collaboration to accelerate AI adoption among santripreneurs